9 - Indicators of Higher Education and the Public Good in Africa: A Dashboard Approach - Molebatsi, Palesa; McCowan, Tristan (Journal of Higher Education in Africa, 2022)
Indicators and metrics have gained increasing prominence in international higher education in recent years, and global rankings have become a powerful force in shaping ideas of what the university is and should be. Yet these measures do a poor job of capturing the broad role of the institution, and particularly in recognising its actions in promoting the public good and addressing inequalities. African higher education institutions have struggled to perform well in the conventional rankings, whose indicators rely on extensive resources for high-level research. This article explores the possibilities of alternative metrics for understanding the public good contribution of universities in the context of four African countries: Ghana, Kenya, Nigeria and South Africa. After assessing the shortcomings of the existing indicators and metrics, and the challenges of the availability of data, it puts forward a dashboard approach as a possible new model. Dashboards have the advantage of avoiding the conflation of diverse qualities of importance and allow different profiles of an institution to be compared. The article proposes six main elements for the dashboard: solidarity with society, equitable access and deliberative space (which correspond to the intrinsic notion of public good and graduate destinations, knowledge production and community engagement (which correspond to instrumental notions). Finally, the challenges of implementing public good metrics in practice are discussed.